Effects of ICT Integration in Teaching Using Learning Activities - Toma, Florentina; Ardelean, Andreea; Grădinaru, Cătălin; Nedelea, Alexandru; Diaconu, Daniel Constantin (Sustainability, 2023)
Progress in schooling using competence-based teaching for students is a priority in setting up a quality-centered educational process. Thus, using ICT tools as teaching–learning techniques represents an important objective in reaching scholastic performance and the capacity to offer students various experiences in teaching. Starting with an analysis of research on integrating ICT tools in the educational environment, this study is aimed at presenting teaching opportunities for all students, seeing education through the lens of those instruments specific to a secondary school level, referencing the subject of geography. The applied research design includes mixed methods applied to a total of 674 students, based on results received before and after a written evaluation, to determine the level of knowledge of the students. The present study evaluates the learning environment in which a successful and practical integration of ICT tools is anticipated in the teaching and learning process, from the perspective of the comparative measurement of the impact on the tests, resulting from the formative assessment. The conducted experiment and the Google Forms questionnaires suggest, through the degree of involvement of all students, how technology can facilitate the teaching–learning process. The results showed that there are statistically significant differences between the experimental and the control group, and that information and communication technologies (ICT) represent an important tool for improving performance and developing participatory skills, having the ability to provide students with positive results.